2014
DOI: 10.1073/pnas.1415174111
|View full text |Cite|
|
Sign up to set email alerts
|

Intestinal permeability, gut-bacterial dysbiosis, and behavioral markers of alcohol-dependence severity

Abstract: Alcohol dependence has traditionally been considered a brain disorder. Alteration in the composition of the gut microbiota has recently been shown to be present in psychiatric disorders, which suggests the possibility of gut-to-brain interactions in the development of alcohol dependence. The aim of the present study was to explore whether changes in gut permeability are linked to gut-microbiota composition and activity in alcohol-dependent subjects. We also investigated whether gut dysfunction is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
645
6
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 741 publications
(760 citation statements)
references
References 70 publications
29
645
6
11
Order By: Relevance
“…This further suggests a role of the microbiomegut-brain axis in AUD. The low intestinal permeability group demonstrated reduced severity and duration of psychological symptoms, while the high intestinal permeability group showed persistent ADrelated behavioral changes throughout short-term abstinence, despite intestinal permeability recovery (Leclercq et al, 2014b). Two possible conclusions regarding the persistence of symptoms in the high intestinal permeability group were proposed (de Timary et al, 2015).…”
Section: Critical View Of the Studies Reportedmentioning
confidence: 99%
See 2 more Smart Citations
“…This further suggests a role of the microbiomegut-brain axis in AUD. The low intestinal permeability group demonstrated reduced severity and duration of psychological symptoms, while the high intestinal permeability group showed persistent ADrelated behavioral changes throughout short-term abstinence, despite intestinal permeability recovery (Leclercq et al, 2014b). Two possible conclusions regarding the persistence of symptoms in the high intestinal permeability group were proposed (de Timary et al, 2015).…”
Section: Critical View Of the Studies Reportedmentioning
confidence: 99%
“…By checking auto-Ab levels and sequence homology comparisons between ED and healthy participants, the studies reviewed support the possibility that gut microbiota-driven dysregulation of neuroendocrine control of appetite leads to behavioral profiles associated with food intake in patients with EDs. With respect to AUD, chronic alcohol use induces dysbiosis and increased intestinal permeability in only a subset of alcohol dependent patients (Bode and Bode, 2003;Mutlu et al, 2012), allowing microbial metabolites to enter peripheral and central circulation and impact behavioral correlates such as alcohol craving (Leclercq et al, 2014b). Thus, chronic excessive alcohol use is necessary, but not sufficient to cause gut dysfunction in alcohol dependent patients (Mutlu et al, 2012;Leclercq et al, 2014b).…”
Section: Critical View Of the Studies Reportedmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking cessation has also been suggested to influence the gut microbiota but other factors than smoking cessation per se, such as weight gain following smoking cessation, may confound this relationship (50). Recently, it has been shown that some alcohol-dependent subjects demonstrate increased intestinal permeability and alterations of the gut microbiota at the compositional and functional level, suggesting that alcohol may also play an important role (51).…”
Section: Type 2 Diabetes and Gut Microbiota: A Word Of Cautionmentioning
confidence: 99%
“…10,11 ) and the development of profound social impairment as observed in autistic spectrum disorders. [12][13][14] The paper we are commenting on here, 15 even though focusing on alcohol-dependence, also relates to depression and anxiety, as these Keywords: alcohol dependence, alcohol use disorders, behavior, depression, gut permeability, gut-brain axis, gut microbiota, leaky gut, negative reinforcement symptoms are an important dimension of alcohol-dependence. In the first part of the discussion, these aspects will be evoked at the light of the negative reinforcement process, that is a major dimension of the addictive process, 16 especially in chronic addiction.…”
Section: Introductionmentioning
confidence: 99%